Preparation method and application of carbon-based composite wave absorbing material
By using ferrite clusters as precursors to recombine with carbon materials, the problems of high density and poor recombination uniformity of traditional iron-based materials are solved, and effective regulation of the absorbing frequency band and efficient electromagnetic wave absorption performance are achieved.
Patent Information
- Application Number
- CN202310274450.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-20
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-03-20
AI Technical Summary
Traditional iron-based materials have high density and are difficult to recombine evenly with dielectric materials, making it difficult to control the wave absorbing frequency band.
Ferrite clusters are used as a new precursor to grow magnetic iron-based metal particles in situ through hydrothermal reactions, and uniformly recombined with carbon materials such as graphene oxide or carboxylated carbon nanotubes to regulate the size and distribution of magnetic particles to achieve effective regulation of the absorption frequency band.
The prepared ferrite cluster-derived magnetic particles/carbon-based composite absorbing materials achieve strong electromagnetic wave absorption and wide effective absorption bandwidth at thinner thicknesses, with reflection loss value up to -73.2dB and effective absorption bandwidth up to 5.6GHz, meeting the requirements of thin thickness, wide absorption frequency band, light mass and high absorption strength.
Smart Images

Figure CN116285886B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of a carbon-based composite wave-absorbing material, belonging to the technical field of wave-absorbing materials. Background Art
[0002] Electromagnetic wave absorbing materials have received extensive attention in both the civilian and military fields. In the civilian field, electromagnetic interference and radiation pollution not only affect the normal operation of electronic equipment, but also threaten people's lives and health. Absorbing materials with excellent performance can protect electronic equipment and human bodies from the harm of electromagnetic wave radiation. In the military field, absorbing materials are key technical materials for radar stealth and have always been highly valued by all countries. With the advancement of science, the requirements for electromagnetic wave absorbing materials are getting higher and higher. It is urgent to develop lightweight, strong absorption, and broadband absorbing materials.
[0003] At present, it is a hot topic to effectively combine dielectric loss-type materials with traditional magnetic loss-type materials to construct absorbing materials with dielectric-magnetic dual loss mechanisms. Iron-based materials, as magnetic loss-type absorbing materials, usually have strong absorption of electromagnetic waves in the low-frequency region, but their density is high and the loss mechanism is single, making it difficult to achieve broadband absorption. Carbon materials, as the most common dielectric materials, not only have excellent electrical loss characteristics but also have low density. At the same time, nano-carbon materials reported in recent years, such as graphene and carbon nanotubes, have easily modified functional groups on the surface and are easy to be compounded with other materials. Therefore, compounding carbon materials with iron-based materials is an effective strategy for preparing lightweight, high-performance absorbing materials, and a large number of researchers are now studying related content. In terms of patents, the Chinese patent with the patent publication number CN 110964480 A discloses a graphene-based magnetic thermal conductive wave absorbing material, which is compounded with a magnetic material and a dielectric material by an improved solvothermal method, in-situ grown on the graphene surface by ferroferric oxide, and then coated with a thermal conductive inorganic nanomaterial to obtain a graphene oxide / ferroferric oxide / zinc oxide composite material. The material has excellent wave absorbing performance, with a reflection loss value as low as -43.2dB at 7.05GHz and an effective absorption bandwidth of 2.2GHz. In addition to ferroferric oxide, ferrite is also a common iron-based material. A Chinese patent with the patent authorization number CN 102876288 B discloses a method for preparing a graphene / barium ferrite composite absorber. The graphene dispersion and barium ferrite suspension are uniformly mixed by an environmentally friendly and simple ultrasonic dispersion and blending method, and then a graphene-loaded magnetic particle barium ferrite composite absorber is obtained by hydrothermal reaction and washing and drying. The reflection loss value of the material is -22.09dB at a frequency of 12.74GHz and a sample thickness of 2mm, and the effective absorption bandwidth is 4.0GHz (11.13-15.13GHz). In the literature, Shu et al. prepared a multi-walled carbon nanotube / zinc ferrite (MWCNTs / ZnFe2O4) hybrid composite material by a simple one-step solvothermal method.The ZnFe2O4 microspheres are fixed on the surface of multi-walled carbon nanotubes to connect them and form a three-dimensional conductive network in the composite material. The electromagnetic wave absorption performance of the MWCNTs / ZnFe2O4 composite material is optimized by adjusting the size of the microspheres and the length of the multi-walled carbon nanotubes. At 13.4GHz, its minimum reflection loss value is -55.5dB, the effective absorption bandwidth is 3.6GHz, and the thickness is 1.5mm (reference: Fabrication of 3D net-like MWCNTs / ZnFe2O4 hybrid composites as high-performance electromagnetic wave absorbers. Chemical Engineering Journal, 2018, 337, 242-255.). Zhang et al. designed a lightweight hybrid structure of magnetic CoFe2O4 hollow particles modified with multi-walled carbon nanotubes (MWCNTs) / reduced graphene oxide (RGO). This carbon-coated reduced graphene oxide / magnetic CoFe2O4 hollow particles modified multi-walled carbon nanotube composite material exhibits significant microwave absorption performance when the filling amount is 20wt%, due to its multi-phase composite special nanostructure, more pores, higher specific surface area and synergistic effect. At 11.6GHz, the minimum reflection loss reaches -46.8dB with a thickness of 1.6mm. At the same time, by adjusting the thickness within the range of 1.2mm-4mm, the material can achieve effective absorption in a wider frequency range (4.9-18GHz) (reference: Preparation and microwave absorption properties of asphalt carboncoated reduced graphene oxide / magnetic CoFe2O4 hollow particles modifiedmulti-wall carbon nanotube composites.Journal of Alloys and Compounds, 2017, 723, 912-921.).
[0004] Although many researchers have studied iron-based magnetic materials / carbon composite absorbing materials, the composite uniformity between the two still needs to be improved, and the absorbing frequency band of the composited material is still difficult to control. Based on this, the present invention selects ferrite clusters as a new precursor to provide ultra-strong magnetic loss, while making full use of the intrinsic charge properties of ferrite clusters to achieve uniform composite with carbon materials. By changing the type and content of carbon materials to control the size and distribution of magnetic particles, effective control of the absorbing frequency band is ultimately achieved. The present invention optimizes and constructs a new type of ferrite cluster-derived magnetic particle / carbon-based composite absorbing material with dielectric-magnetic dual loss through a simple preparation process to meet a wider range of applications. Summary of the invention
[0005] The purpose of the present invention is to solve the problems that traditional iron-based materials have high density, are difficult to be uniformly compounded with dielectric materials, and have difficult to control the wave absorption frequency band. The present invention provides a method for preparing a magnetic particle / carbon-based composite wave absorbing material using ferrite clusters as a novel precursor. The method uses carbon materials to reduce the density of traditional iron-based materials to achieve the requirement of light weight, and at the same time fully utilizes the intrinsic charge properties of ferrite clusters to achieve uniform compounding with carbon materials. By changing the type and content of carbon materials, the size and distribution of magnetic particles and the wave absorption frequency band of the final composite wave absorbing material are regulated to achieve effective absorption of electromagnetic waves in different frequency bands. The ferrite cluster-derived iron-based particle / carbon-based composite wave absorbing material finally prepared meets the requirements of thin thickness, wide wave absorption frequency band, light weight, and high absorption intensity.
[0006] In order to achieve the above-mentioned object, the present invention provides a carbon-based composite absorbing material, which is a composite absorbing material prepared by in-situ growing a precursor ferrite cluster in a precursor ferrite cluster reaction solution by a hydrothermal reaction, and uniformly loading magnetic iron-based metal particles derived from the ferrite cluster; the carbon-based material is graphene oxide and / or carboxylated carbon nanotubes, and the precursor ferrite cluster is [Fe 15 O6(tea)8Cl6](OH)(ClO4)2, where tea is triethanolamine (C6H 15 NO3).
[0007] Preferably, the preparation method of the precursor iron oxide cluster reaction solution comprises: dissolving ferric chloride and ferrous perchlorate in methanol, then adding triethanolamine and triethylamine and stirring overnight in a dark environment to obtain the precursor iron oxide cluster reaction solution.
[0008] The present invention also provides a method for preparing the above carbon-based composite absorbing material, comprising the following steps:
[0009] Step 1: adding nano carbon-based materials to the precursor ferrite cluster reaction solution for ultrasonic dispersion;
[0010] Step 2: In-situ compounding is performed by a one-step hydrothermal method to prepare an iron oxide cluster / carbon-based composite material precursor, which is filtered and dried at room temperature for later use;
[0011] Step 3: Obtain the ferrite cluster-derived magnetic particle / carbon-based composite absorbing material by calcination under an inert atmosphere.
[0012] Preferably, the preparation method of the precursor iron oxide cluster reaction solution in step 1 comprises: dissolving ferric chloride and ferrous perchlorate in methanol, then adding triethanolamine and triethylamine and stirring overnight in a dark environment to obtain the precursor iron oxide cluster reaction solution.
[0013] Preferably, the mass ratio of the carbon-based material added in step 1 to the volume ratio of the precursor ferrite cluster reaction solution is: 5-15 mg: 10-15 mL; the iron ions (in terms of Fe 2+ and Fe 3+ The total concentration of Fe is 0.01 to 0.1 g / mL. 2+ and Fe 3+ The molar ratio is 1.1~2.2:1~1.5.
[0014] Preferably, the process conditions for the in-situ compounding by the hydrothermal method in step 2 are: reacting at 80-150° C. for 20-36 hours, and then cooling to room temperature at a cooling rate of 3-5° C. / min.
[0015] Preferably, the process conditions for calcination in step 3 are: heating rate 4-6°C / min, calcination temperature 700-1000°C, and holding time 1-3h.
[0016] The present invention also provides the use of the carbon-based composite absorbing material or the carbon-based composite absorbing material prepared by the preparation method in absorbing electromagnetic waves.
[0017] The present invention also provides the use of the above-mentioned carbon-based composite absorbing material, or the carbon-based composite absorbing material prepared by the above-mentioned preparation method as a stealth material for weapons and equipment and / or military facilities.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] (1) The novel carbon-based composite absorbing material prepared by the present invention can achieve strong electromagnetic wave absorption and wide effective absorption bandwidth at a relatively thin thickness; some preferred examples can show that in the frequency range of 2-18 GHz, the reflection loss value of the prepared absorbing material can reach a minimum of -73.2 dB, the frequency is 8.4 GHz, and the thickness is 2.3 mm; some preferred examples can show that the effective absorption bandwidth of the prepared absorbing material can reach up to 5.6 GHz, the reflection loss value is -56.2 dB, and the thickness is 1.52 mm; by changing the type and content of the composite carbon material and combining with regulating the sample thickness, the prepared composite material can achieve ultra-wide electromagnetic wave effective absorption in the range of 2.97 GHz-18 GHz; in addition, by simulating the radar scattering cross section of the material through electromagnetic simulation, it is verified that the material has practical application potential in the field of radar stealth;
[0020] (2) The novel carbon-based composite absorbing material prepared by the present invention selects ferrite clusters as novel precursors to provide strong magnetic loss. By utilizing the intrinsic positive charge property of the selected ferrite clusters, the ferrite clusters can be tightly composited with graphene oxide or carboxylated carbon nanotubes having a rich surface of negatively charged active sites through electrostatic forces, thereby constructing a dielectric-magnetic dual-loss absorbing material;
[0021] (3) The novel carbon-based composite absorbing material prepared by the present invention can effectively control the microscopic morphology of the material by adjusting the type and content of the carbon material; some preferred examples can show that when an appropriate amount of carbon material is added, a good confinement effect can be produced to limit the growth of magnetic particles derived from ferrite clusters, and effectively inhibit agglomeration to achieve uniform distribution of magnetic particles;
[0022] (4) The novel carbon-based composite absorbing material prepared by the present invention effectively improves the disadvantage of high density of traditional iron-based materials, realizes strong absorption and wide-band absorption at ultra-thin thickness, and has excellent impedance matching performance; the preparation method of the present invention is simple and easy to operate, and the prepared novel carbon-based composite absorbing material has stable performance and good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is a SEM image of the ferrite cluster-derived magnetic particle / reduced graphene oxide composite absorbing material prepared in Example 3;
[0024] Figure 2 is a reflection loss diagram of the ferrite cluster derived magnetic particle / reduced graphene oxide composite absorbing material prepared in Example 3 after adjusting the thickness;
[0025] Figure 3 is the XRD pattern of the ferrite cluster derived magnetic particle / reduced graphene oxide series composite absorbing material prepared in Examples 1-4;
[0026] Figure 4is a SEM image of the ferrite cluster derived magnetic particle / carbon nanotube composite absorbing material prepared in Example 7;
[0027] Figure 5 is a reflection loss diagram of the ferrite cluster derived magnetic particle / carbon nanotube composite absorbing material prepared in Example 7 after adjusting the thickness;
[0028] Figure 6 is the XRD pattern of the ferrite cluster derived magnetic particle / carbon nanotube series composite absorbing material prepared in Examples 5-8;
[0029] Figure 7 is a statistical graph of radar cross section (RCS) reduction values of the ferrite cluster-derived magnetic particles / reduced graphene oxide composite absorbing materials prepared in Examples 1-4 at different scanning angles;
[0030] Figure 8 It is a statistical graph of radar cross section (RCS) reduction values of the ferrite cluster derived magnetic particle / carbon nanotube composite absorbing material prepared in Examples 5-8 at different scanning angles. DETAILED DESCRIPTION
[0031] In order to make the present invention more clearly understood, preferred embodiments are described in detail below with reference to the accompanying drawings.
[0032] Example 1
[0033] A method for preparing a composite wave absorbing material of ferrite cluster-derived magnetic particles / reduced graphene oxide comprises the following steps:
[0034] 1. First, weigh 0.1-0.2g of anhydrous FeCl3 and 0.2-0.3g of Fe(ClO4)2·6H2O and dissolve them in 20-30mL of methanol. Stir thoroughly to form an orange solution. Add 0.1-0.2mL of triethanolamine dropwise while stirring, then add 0.2-0.5mL of triethylamine dropwise while stirring. Stir the obtained solution at room temperature and protect it from light overnight to obtain a dark orange solution. Filter to obtain a clear precursor solution.
[0035] 2. Then, take 10-15mL of the precursor solution, add 5mg of graphene oxide, and perform ultrasonication for 20-30min to fully disperse and mix, and then perform a hydrothermal reaction. The conditions of the hydrothermal reaction are: temperature 80-150℃, holding time 20-36h, cooling rate 3-5℃ / min, and then stand for a period of time, collect after filtration to obtain the iron oxide cluster / reduced graphene oxide composite material precursor, evaporate and dry at room temperature for 24-48h.
[0036] 3. The dried iron oxide cluster / reduced graphene oxide composite precursor powder is calcined in an inert atmosphere of nitrogen or argon. The calcination conditions are: heating at a heating rate of 4-6°C / min to 700-1000°C for 1-3h to finally obtain an iron oxide cluster-derived magnetic particle / reduced graphene oxide composite absorbing material.
[0037] Measurement results: When the prepared ferrite cluster-derived magnetic particles / reduced graphene oxide composite absorbing material has a matching thickness of 4.99 mm and a frequency of 17.8 GHz, the reflection loss value is as low as -12.6 dB, and the effective absorption bandwidth can reach 0.32 GHz.
[0038] Example 2
[0039] The difference between this embodiment and embodiment 1 is that the content of graphene oxide added in step 2 is 10 mg, and the rest is the same as embodiment 1.
[0040] Measurement results: When the prepared ferrite cluster-derived magnetic particles / reduced graphene oxide composite absorbing material has a matching thickness of 4.93 mm and a minimum reflection loss value of -54.3 dB at a frequency of 17.5 GHz. By adjusting the thickness, the effective absorption bandwidth can reach a maximum of 2.1 GHz.
[0041] Example 3
[0042] The difference between this embodiment and embodiment 1 is that the content of graphene oxide added in step 2 is 12.5 mg, and the rest is the same as embodiment 1.
[0043] Measurement results: When the prepared ferrite cluster-derived magnetic particles / reduced graphene oxide composite absorbing material has a matching thickness of 1.52 mm and a reflection loss value of -56.2 dB at a frequency of 14.7 GHz, the effective absorption bandwidth can reach 5.6 GHz.
[0044] Figure 1 This is a SEM image of the ferrite cluster-derived magnetic particles / reduced graphene oxide composite absorber obtained in step 3 of this embodiment. The sample shows a morphology of magnetic iron particles embedded in flaky GO, which is caused by the confinement effect of graphene oxide, indicating that the addition of an appropriate amount of graphene oxide can prevent the aggregation of magnetic particles and effectively regulate the size and distribution of magnetic particles, which is beneficial to the absorbent performance of the composite material.
[0045] Figure 2 This is a reflection loss diagram of the ferrite cluster derived magnetic particle / reduced graphene oxide composite absorbing material obtained in step 3 of this embodiment after adjusting the thickness.
[0046] Example 4
[0047] The difference between this embodiment and embodiment 1 is that the content of graphene oxide added in step 2 is 15 mg, and the rest is the same as embodiment 1.
[0048] Measurement results: When the prepared ferrite cluster-derived magnetic particles / reduced graphene oxide composite absorbing material has a matching thickness of 3.43 mm and a reflection loss value of -53.5 dB at a frequency of -53.5 GHz, the effective absorption bandwidth can reach 4.4 GHz by adjusting the thickness to 1.53 mm.
[0049] According to the test results of the absorbing performance of the absorbing materials prepared in Examples 1-4, it can be seen that Example 3, in which the ferrite cluster is composited with 12.5 mg of graphene oxide, is a preferred embodiment of the ferrite cluster-derived magnetic particles / reduced graphene oxide composite absorbing material. The addition of an appropriate amount of graphene oxide has a confining effect on the magnetic particles derived from the ferrite cluster, and at the same time, the intrinsic charge properties of the ferrite cluster enable it to be more uniformly composited with the graphene oxide rich in negatively charged functional groups on the surface. The absorbing material prepared in Example 3 has excellent absorbing performance. When the matching thickness is 1.52 mm, the reflection loss value is as low as -56.2 dB, and the effective absorption bandwidth can reach 5.6 GHz.
[0050] Figure 3 This is the XRD diagram of the ferrite cluster derived magnetic particle / reduced graphene oxide series composite absorbing material obtained in Examples 1-4. The test results show that the crystalline phase mainly includes Fe, Fe3C and C phases.
[0051] Example 5
[0052] The difference between this embodiment and embodiment 1 is that the carbon material added in step 2 is carboxylated carbon nanotubes, and the amount added is 5 mg. The other aspects are the same as those in embodiment 1.
[0053] Measurement results: When the prepared ferrite cluster-derived magnetic particle / carbon nanotube composite absorbing material has a matching thickness of 1.62 mm, the reflection loss value is as low as -22.87 dB at a frequency of 13.4 GHz. By adjusting the thickness to 1.35 mm, the effective absorption bandwidth can reach 3.2 GHz.
[0054] Example 6
[0055] The difference between this embodiment and embodiment 1 is that the carbon material added in step 2 is carboxylated carbon nanotubes, and the amount added is 10 mg. The other aspects are the same as those in embodiment 1.
[0056] Measurement results: The prepared ferrite cluster derived magnetic particle / carbon nanotube composite absorbing material has a minimum reflection loss value of -51.95dB when the matching thickness is 2.45mm and the frequency is 8GHz. By adjusting the thickness to 1.25mm, the widest effective absorption bandwidth can reach 3.5GHz.
[0057] Example 7
[0058] The present embodiment is different from the embodiment 1 in that the carbon material added in step 2 is carboxylated carbon nanotubes, and the amount added is 12.5 mg. The rest is the same as the embodiment 1.
[0059] Measurement results: The prepared ferrite cluster-derived magnetic particle / carbon nanotube composite absorbing material has a minimum reflection loss value of -73.2dB when the matching thickness is 2.26mm and the frequency is 8.4GHz. By adjusting the thickness to 1.21mm, the widest effective absorption bandwidth can reach 3.6GHz.
[0060] Figure 4 This is a SEM image of the ferrite cluster derived magnetic particle / carbon nanotube composite absorbing material obtained in step 3 of this embodiment. The sample shows the morphology of magnetic iron particles attached to filamentous carbon nanotubes, indicating that carbon nanotubes can also play a certain confinement role, which is beneficial to the absorbing performance of the composite material.
[0061] Figure 5 This is a graph of the reflection loss of the ferrite cluster derived magnetic particle / carbon nanotube composite absorber with controlled thickness obtained in step 3 of this embodiment. The composite material prepared in this embodiment can achieve effective absorption in an ultra-wide frequency range (2.97-18 GHz) by controlling the thickness in the range of 1 mm-5 mm.
[0062] Example 8
[0063] The present embodiment is different from the embodiment 1 in that the carbon material added in step 2 is carboxylated carbon nanotubes, and the amount added is 15 mg. The other aspects are the same as those in the embodiment 1.
[0064] Measurement results: The prepared ferrite cluster-derived magnetic particle / carbon-based composite absorbing material has a minimum reflection loss value of -22.17dB when the matching thickness is 1.04mm and the frequency is 3.1GHz. By adjusting the thickness to 1.17mm, the effective absorption bandwidth can reach 4GHz.
[0065] According to the test results of the absorbing performance of the absorbing materials prepared in Examples 5-8, it can be seen that the composite of the iron oxide cluster and 12.5 mg of carboxylated carbon nanotubes in Example 7 is a preferred embodiment of the iron oxide cluster-derived magnetic particles / carbon nanotube composite absorbing material. The absorbing material prepared in Example 7 has a super strong electromagnetic wave absorption ability. When the frequency in the intermediate frequency region is 8.4 GHz, its reflection loss can reach -73.2 dB, and the matching thickness is only 2.26 mm. By adjusting the sample thickness to 1.21 mm, its maximum effective bandwidth is 3.6 GHz.
[0066] Figure 6This is the XRD diagram of the ferrite cluster derived magnetic particle / carbon nanotube series composite absorbing material obtained in Example 5-8. The test results show that the crystalline phase is mainly Fe phase.
[0067] The carbon materials selected for Examples 1-4 and 5-8 are graphene oxide and carboxylated carbon nanotubes, respectively. It can be seen from the test results of the wave absorption performance of the two series of samples that the wave absorption performance has been significantly improved. The introduction of carbon materials not only improves the dielectric properties of the material, but also improves the impedance matching, while enabling the composite material to meet the demand for lightweight. In addition, the introduction of carbon materials of different types and contents and the ferrite cluster composite can effectively regulate the size distribution and wave absorption frequency band of the magnetic particles, and by regulating the thickness of the sample, the composite material can effectively absorb in the S, C, X, and Ku bands, achieving ultra-wideband electromagnetic wave absorption.
[0068] Electromagnetic simulations were performed on the composite materials prepared in implementation cases 1-8, and the radar scattering cross section of the ferrite cluster-derived magnetic particles / carbon-based composite absorbing materials in actual applications was simulated to verify the practical applicability of the absorbing materials. Figure 7 and Figure 8 The radar cross section (RCS) reduction value statistics of the composite materials prepared in Examples 1-4 and Examples 5-8 at different scanning angles are shown in Figure 1. The radar cross section (RCS) reduction value of the composite material prepared in Example 7 is the largest, which is 34.22 dB m 2 This indicates that the composite material prepared in Example 7 has low reflection and has the best stealth effect when coated on the target to be detected.
[0069] The above embodiments are only preferred embodiments of the present invention and are not any formal or substantial limitations of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the present invention, and these improvements and supplements should also be regarded as the scope of protection of the present invention.
Claims
1. A carbon-based composite absorbing material, characterized in that: The composite wave absorbing material is prepared by taking carbon-based material as matrix, in-situ growing precursor ferrite clusters by hydrothermal reaction in precursor ferrite cluster reaction solution, and uniformly loading magnetic iron-based metal particles derived from ferrite clusters; the carbon-based material is graphene oxide and / or carboxylated carbon nanotubes, the precursor ferrite cluster is [Fe 15 O6(tea)8Cl6](OH)(ClO4)2, where tea is triethanolamine; The method for preparing the carbon-based composite absorbing material comprises the following steps: Step 1: adding nano carbon-based materials to the precursor ferrite cluster reaction solution for ultrasonic dispersion; Step 2: In-situ compounding is performed by a one-step hydrothermal method to prepare an iron oxide cluster / carbon-based composite material precursor, which is filtered and dried at room temperature for later use; Step 3: obtaining the ferrite cluster-derived magnetic particle / carbon-based composite absorbing material by calcining in an inert atmosphere; The preparation method of the precursor iron oxide cluster reaction liquid comprises: dissolving ferric chloride and ferrous perchlorate in methanol, then adding triethanolamine and triethylamine and stirring overnight under light-proof conditions to obtain the precursor iron oxide cluster reaction liquid.
2. The method for preparing the carbon-based composite absorbing material according to claim 1, characterized in that: The following steps are involved: Step 1: adding nano carbon-based materials to the precursor ferrite cluster reaction solution for ultrasonic dispersion; Step 2: In-situ compounding is performed by a one-step hydrothermal method to prepare an iron oxide cluster / carbon-based composite material precursor, which is filtered and dried at room temperature for later use; Step 3: Obtain the ferrite cluster-derived magnetic particle / carbon-based composite absorbing material by calcination under an inert atmosphere.
3. The method for preparing the carbon-based composite absorbing material according to claim 2, characterized in that: In the step 1, the volume ratio of the added mass of the carbon-based material to the precursor ferrite cluster reaction solution is: 5-15 mg: 10-15 mL; the concentration of iron ions in the precursor ferrite cluster reaction solution is 0.01-0.1 g / mL.
4. The method for preparing a carbon-based composite absorbing material according to claim 2, characterized in that: The process conditions for the in-situ compounding by the hydrothermal method in step 2 are: reacting at 80-150° C. for 20-36 hours, and then cooling down to room temperature at a cooling rate of 3-5° C. / min.
5. The method for preparing the carbon-based composite absorbing material according to claim 2, characterized in that: The process conditions for calcination in step 3 are: heating rate 4-6°C / min, calcination temperature 700-1000°C, and holding time 1-3h.
6. Use of the carbon-based composite absorbing material according to claim 1 in absorbing electromagnetic waves.
7. Use of the carbon-based composite absorbing material according to claim 1 as a stealth material for weapons and equipment and / or military facilities.
Citation Information
Patent Citations
Graphite / barium ferrite composite wave-absorbing material and preparation method thereof
CN102876288B
Graphene oxide / ferroferric oxide / zinc oxide composite material and preparation method thereof, and graphene-based magnetic heat-conducting wave-absorbing material
CN110964480A
Novel composite of iron compound and graphene oxide
CN107531489A
Polyimide / multi-walled carbon nanotube / nano ferroferric oxide composite aerogel and preparation method thereof
CN111607228A